Bangla character recognition for Android devices - Manzur, Shahrin; Islam, Shafiqul; Foysal, Abu; Chowdhury, Aparajita (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.